(untitled) (Revista Brasileira de Ciências Farmacêuticas, 2005)
The antioxidant activity of stem-bark extracts from Stryphnodendron obovatum Benth., including fractions and isolated compounds, was evaluated by DPPH in thin-layer chromatography. All the fractions and isolated compounds showed antioxidant activity. Antifungal activity was determined by the minimum inhibitory concentration (MIC) and minimum fungicidal concentration (MFC) against the yeasts Candida albicans, Candida parapsilosis, Candida krusei and Candida tropicalis. All extracts (CE, EtOAc and FW), subfractions (F1-F12) and the compounds I, II and III were inactive against the yeasts. Against C. parapsilosis and C. albicans, fractions F13-15 and F20 showed moderate antifungal activity, and fractions F16-19 and F21-22 showed good activity. Chemical isolation of the ethyl-acetate fraction resulted in the identification of three compounds: epigallocatechin, gallocatechin and epigallocatechin-(4;b®;8)-gallocatechin.